The role of future University in Malaysia for the well-being and economic development of youth in Comoros through humanizing education - Ahamada, Abdoulatuf; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
Education is one of the most important factors for the development and well-being of a country. It reduces poverty, boosts economic growth and increases income. It increases opportunities for young people to lead healthy lives, reduces maternal mortality and fights diseases such as HIV and AIDS. This paper examines the role of humanizing education and how it can contribute to the fight against poverty while enhancing the well-being of youth in Comoros. Also this paper discusses on how humanizing education can contribute to enhancing the youth satisfaction and loyalty to their country. Finally, this paper offers a possible business model of a Malaysian University of the Future for humanizing entrepreneurship education in Comoros in order to nurture youths with the knowledge, skills and virtues. These youths can start their own business; create employment for others, and sustaining harmonious and caring citizens.